Social Network Ties And Knowledge Sharing - Chamiappan, Bathmaperia (2008)
Sharing knowledge and information is also an important factor in discourses on electronic government(e-government) ,national security, and human capital management. The present study aims to study the role of social network ties on individual knowledge sharing in an organization.